Vagus nerve modulation using focused pulsed ultrasound: Potential applications and preliminary observations in a rat. Issue 1 (March 2014) - Juan, Eduardo J.; González, Rafael; Albors, Gabriel; Ward, Matthew P.; Irazoqui, Pedro
ABSTRACT The use of focused ultrasonic waves to modulate neural structures has gained recent interest due to its potential in treating neurological disorders noninvasively. While several articles have focused on the use of ultrasound neuromodulation on peripheral nerves, none of these studies have been performed on the vagus nerve. We present preliminary observations on the effects of focused pulsed ultrasound (FPUS) on the conduction of the left cervical vagus nerve of a Long Evans rat. Ultrasound energy was applied at a frequency of 1.1 MHz, and at spatial‐peak, temporal average intensities that ranged from 13.6 to 93.4 W/cm2. Vagus nerve inhibition was observed in most cases. Results of this preliminary study suggested that there is a proportional relationship between acoustic intensity and the level of nerve inhibition.